Funding for sustainable development of rural communities: European experience - Liudmyla Romanchuk; Iryna Abramova; Yuliia Moroz; Pavlo Poplavskyi; Ihor Svitlyshyn (Agricultural and Resource Economics)
Purpose. The study aims to assess the European experience of funding for sustainable development of rural communities and the possibility of its implementation in Ukraine.